2001
DOI: 10.1038/35066504
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the bacterial flagellar protofilament and implications for a switch for supercoiling

Abstract: The bacterial flagellar filament is a helical propeller constructed from 11 protofilaments of a single protein, flagellin. The filament switches between left- and right-handed supercoiled forms when bacteria switch their swimming mode between running and tumbling. Supercoiling is produced by two different packing interactions of flagellin called L and R. In switching from L to R, the intersubunit distance ( approximately 52 A) along the protofilament decreases by 0.8 A. Changes in the number of L and R protofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
424
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 453 publications
(435 citation statements)
references
References 44 publications
7
424
1
3
Order By: Relevance
“…The location of the MxiH β-hairpin is topologically analogous to that of the β-hairpin in domain D1 of flagellin in the flagellar filament (34). In flagellin, the β-hairpin is crucial to the polymorphic supercoiling of the filament, which involves a 0.8 Å change in the axial repeat along the 11-start protofilament, in response to a change in the direction of motor rotation (34). The comparison of the two protofilament conformations of the flagellar filament called L and R type has shown that the conformational change of flagellin involved in the polymorphic supercoiling of the filament is the switch in the orientation of the outer core domains relative to the invariant structure of the tubular assembly of the inner core domains (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of the MxiH β-hairpin is topologically analogous to that of the β-hairpin in domain D1 of flagellin in the flagellar filament (34). In flagellin, the β-hairpin is crucial to the polymorphic supercoiling of the filament, which involves a 0.8 Å change in the axial repeat along the 11-start protofilament, in response to a change in the direction of motor rotation (34). The comparison of the two protofilament conformations of the flagellar filament called L and R type has shown that the conformational change of flagellin involved in the polymorphic supercoiling of the filament is the switch in the orientation of the outer core domains relative to the invariant structure of the tubular assembly of the inner core domains (35).…”
Section: Discussionmentioning
confidence: 99%
“…The four residues (P44 þ Q51, Y57, and D73) that lead to an inability to transmit the activation signal when altered to alanine (5) lie in positions where they may directly (Y57 and Q51) or indirectly (P44 and D73) affect the orientation or conformation of the β-hairpin. The location of the MxiH β-hairpin is topologically analogous to that of the β-hairpin in domain D1 of flagellin in the flagellar filament (34). In flagellin, the β-hairpin is crucial to the polymorphic supercoiling of the filament, which involves a 0.8 Å change in the axial repeat along the 11-start protofilament, in response to a change in the direction of motor rotation (34).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal, PscF 68-85 helix is essential for polymerization of the full-length PscF, because a mutant lacking this region, PscF 1-67 , behaves as a monomer in gel filtration (SI Fig. 6) and chemical cross-linking experiments (not shown); the C-terminal region of the needle protein has also been shown to be essential for needle assembly in other T3S systems, as well as in the flagellar filament (15,22,23). In addition, PscF 68-85 is highly amphipathic.…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopy images of the bacterial flagellar filament, type III needle, and type IV pilus have revealed that the assembly of these structures involves packing of protein subunits within longitudinal helical arrays; in the case of the flagellum and type IV pilus, hydrophobic interactions have been shown to play key roles in the maintenance of the mechanical infrastructure (14,(23)(24)(25). These observations prompted us to investigate whether hydrophobic amino acids on the amphipathic C terminus of PscF could play a similar role in T3SS needle polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the outer domains of the two structures do look different both in the low-resolution maps and in their atomic structures. In flagellin, there are three outer domains: an ␣-domain near the center, a mostly ␤-(or ␤-hairpin-rich) domain at slightly higher radius, and a ␤-domain at the outside (31). The hook has two outer domains, both having ␤-folds (28) as predicted (30).…”
Section: Discussionmentioning
confidence: 99%